FAMILY TABANIDAE - Wolff, Marta E; Miranda-Esquivel, Daniel Rafael (Zootaxa, 2016)
This catalogue presents 256 species distributed in 32 genera, six tribes and three subfamilies recorded to Colombia. For each species we present the available geographical information and most important references.